Embedded Software Verification and Debugging - Lettnin, Djones; Winterholer, Markus; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2017)
This book provides comprehensive coverage of verification and debugging techniques for embedded software, which is frequently used in safety critical applications (e.g., automotive), where failures are unacceptable. Since the verification of complex systems needs to encompass the verification of both hardware and embedded software modules, this book focuses on verification and debugging approaches for embedded software with hardware dependencies. Coverage includes the entire flow of design, verification and debugging of embedded software and all key approaches to debugging, dynamic, static, and hybrid verification. This book discusses the current, industrial embedded software verification flow, as well as emerging trends with focus on formal and hybrid verification and debugging approaches. Includes in a single source the entire flow of design, verification and debugging of embedded software; Addresses the main techniques that are currently being used in the industry for assuring the quality of embedded software; Includes in-depth coverage of debugging, dynamic, formal and hybrid verification; Discusses emerging trends which focus on formal and hybrid verification and debugging approaches.
An Overview about Debugging and Verification Techniques for Embedded Software -- Embedded Software Debug in Simulation and Emulation Environments for Interface IP -- The Use of Dynamic Temporal Assertions for Debugging -- Automated Reproduction and Analysis of Bugs in Embedded Software -- Model-Based Debugging of Embedded Software Systems -- A Mechanism for Monitoring Driver-Device Communication -- Model Checking Embedded C Software using k-Induction and Invariants -- Scalable and Optimized Hybrid Verification of Embedded Software -- .
Keywords: Electronic circuits; Microprocessors; Computer architecture; Electronics; Electronic Circuits and Systems; Processor Architectures; Electronics and Microelectronics, Instrumentation